Methodical approaches to assessing green infrastructure objects of urban ecosystems - Cherchyk, Larysa M.; Khmarova, Nina I. (My University, 2024)
Topicality. The study of the urban economy development state proves the existence of environmental problems and the need to transition to the principles of environmentally-oriented management, in particular, the implementation of effective environmental and social measures and the increase of green infrastructure facilities to ensure the optimal development of modern cities. This transition suggests changing existing management approaches to new concepts that will ensure balanced and sustainable development of urban areas. Aim and tasks. The aim of the study is to substantiate urban ecosystem`s green infrastructure facilities assessment methodological approaches based on ecosystemic and multifunctional principals and tasks of sustainable development. Materials and Methods. The materials of the article are based on the generalization and systematization of domestic and foreign scientific research. In the research were used the following methods: system-structural analysis; comparative analysis; method of knowledge synthesis, abstraction and analogy, optimization. Research results. The author’s position is that the assessing ecosystem functions results of the urban ecosystem`s green infrastructure should reflect the economic, ecological and social effects of its use and non-use. Taking into account ecosystem functions in the economic evaluation is an opportunity to ensure the adoption of environmentally-oriented decisions while justifying individual projects and development programs: the higher the value of the evaluation then greater the chances that the projects will take into account ecological priorities, implement resource-saving technologies, ensure the integrated use of natural resources, and increase the potential of green infrastructure. Social value is determined by the potential of life support and livelihood, the cultural, historical, aesthetic values of a certain territory, the importance in the formation of the city main areas. Or, in other words, it is determined by the potential opportunity to provide recreation, reproduction of life forces in ecologically favorable conditions. At the same time, it is the investment attractiveness of a certain area, the formation of a favorable microclimate. The ecological value of green infrastructure is determined by the potential opportunities of ecological systems for restoration and ensuring of regulatory and supporting ecosystem services. Conclusion. The development of the green infrastructure assessment methodology should take place with an understanding of the environmental factor growing role for the city’s sustainable development. Therefore, it is necessary to develop evaluation indicators that would reflect the socio-ecological-economic value of green infrastructure and the socio-ecological-economic effect of its creation and operation, the reclaim efficiency of natural resources in various areas of use for choosing the optimal option, since we believe that the natural resources economic evaluation has an undeniable influence on decision-making management regarding their use, and therefore, the formation of comfortable living conditions for the cities population, the substantiation of ecologically oriented programs of urban development in general.
Keywords: natural assets; green infrastructure; urban ecosystem; ecosystem services; economic valu; management decisions; Q56; R11; C83; 332.142.6:911.372.7(045)